1988
DOI: 10.1159/000118433
|View full text |Cite
|
Sign up to set email alerts
|

Allopurinol in Severe Epilepsy

Abstract: We have studied 64 epileptic subjects aged 2–54 years. The subjects were not hyperuricemic and presented daily or weekly severe seizures not controlled by optimal therapy with antiepileptic drugs maintained at ‘therapeutic’ plasma concentrations. Allopurinol at doses ranging from 150 to 300 mg daily was added to a preexisting antiepileptic drug treatment which was never modified throughout a study period of 1 year. After about 1 month of therapy, a progressive decrease of the seizure frequency was observed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
1

Year Published

1990
1990
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 2 publications
0
7
0
1
Order By: Relevance
“…2C) as adjunctive therapy is effective in seizure reduction [172][173][174][175][176], in which allopurinol may act via a decrease of Ado and/or Guo degradation and an HGPRT-induced increase in Ado and Guo levels (Fig. 1) [30,173].…”
Section: Modulation Of Adenosine Levels and Epileptic Activity By Metmentioning
confidence: 99%
“…2C) as adjunctive therapy is effective in seizure reduction [172][173][174][175][176], in which allopurinol may act via a decrease of Ado and/or Guo degradation and an HGPRT-induced increase in Ado and Guo levels (Fig. 1) [30,173].…”
Section: Modulation Of Adenosine Levels and Epileptic Activity By Metmentioning
confidence: 99%
“…Six patients with LGS, from 41 epileptic non-hyperuricemic subjects, aged 2–54 years, already medicated with 2 or 3 AEDs were treated with ALL in doses ranging from 150 to 300 mg daily (DeMarco and Zagnoni 1986). A progressive decrease in the weekly seizure frequency was observed in two-thirds of the cases in this open-label study.…”
Section: Chronic Medical Treatmentmentioning
confidence: 99%
“…Data in humans suggest that the purinergic pathway is altered during an epileptic seizure: an increase in oxipurines was observed in children after episodes of status epilepticus (Manzke et al,198l), and seizures occurring in patients with hyperuricosuria were reported to show a favorable response to allopurinol (Coleman et al, 1974(Coleman et al, , 1986. Based on these findings, uncontrolled clinical trials were performed in patients with refractory epilepsy and yielded conflicting results (DeMarco and Zagnoni, 1986;Guzeva et al, 1988;Sander and Patsalos, 1988;Tada et al, 1991). Our randomized, placebo-controlled trial was designed to investigate the possible antiepileptic action of allopurinol in a large population of patients with refractory epilepsy.…”
mentioning
confidence: 99%